Papel de la "calle de aprendizaje" en la arquitectura escolar española del siglo XX. - Rodríguez Méndez, Francisco Javier (Paedagogica Historica, 2021)
The learning street, understood as a collaborative space and social circuitry within the school, is a concept rooted in Maria Montessori's thinking and further developed by Herman Hertzberger from the 1960s onwards. In a time before the influence of the Italian educator, one may find in Spain precedents to the use of the gallery as an embryonic learning street. The never built project for the Institución Libre de Enseñanza (Free Educational Institution), from 1882, the Cervantes School facilities in Madrid, from 1913, and the six school buildings framed in the 1922 Plan for Madrid included wide corridors specifically designed for such purpose. In the Second Republic, the learning street had already become legitimised by the technical building codes of 1933. The well-meaning and, in many respects, fully justified campaign launched by the journalist Luis Bello in favour of schools, did away with the initiative: proof of such are the 1933 and 1936 plans for school buildings in Madrid. Years later, under the influence of new European currents, the General Education Law of 1970 promoted the adoption of open space typologies in new schools, a measure that also failed, and for similar reasons.